High-temperature-resistant insulating paint and preparation method thereof
Through the blending of silicone combination liquid and acrylic combination liquid and the modification of block emulsifiers and nano-scale fillers, the problems of high-temperature resistant insulating coatings are solved, and lower curing temperature and higher curing temperature are achieved water resistance and insulation properties.
Patent Information
- Application Number
- CN202411168004.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-27
AI Technical Summary
The existing silicone resin-resistant high-temperature insulating coatings have a high curing temperature and poor water resistance, which affects their performance in high-temperature environments.
The silicone combination liquid is blended with the acrylic combination liquid, and modified by block emulsifier and nano-scale filler to reduce the curing temperature and improve the water resistance and insulation properties of the coating.
It significantly reduces the curing temperature of the coating, improves water resistance, heat resistance and insulation ability, and enhances the uniform distribution and performance stability of the coating.
Smart Images

Figure BDA0005008387610000142
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a high temperature resistant insulating coating and a preparation method thereof. Background Art
[0002] In high temperature environments, the oxidation corrosion rate of metal materials accelerates, seriously affecting the mechanical properties and service life of industrial equipment. High temperature resistant coatings generally refer to coatings that do not fall off at temperatures above 200°C and can still maintain appropriate physical and mechanical properties. The application of high temperature resistant coatings can greatly improve the anti-corrosion effect on the substrate in high temperature environments, extend the service life and maintenance cycle of equipment, and save maintenance costs. It has broad application prospects in petrochemical, pipeline, metallurgy, electrical appliances, aerospace and other fields. High temperature resistant coatings are generally divided into two categories: one is organic high temperature resistant coatings represented by silicone resins, and the other is inorganic high temperature resistant coatings. There are fewer varieties of inorganic high temperature resistant coatings, and their mechanical properties are relatively poor. Therefore, organic high temperature resistant coatings have developed rapidly and their application range is becoming more and more extensive.
[0003] In some special applications, the coating needs to have good insulation performance while being able to withstand high temperatures. For example, in high-temperature working environments such as electricity, aerospace, and petrochemicals, the performance of insulating materials is directly related to the safe operation and service life of the equipment. At present, there are many high-temperature resistant insulating coatings on the market, which improve the heat resistance and insulation performance of the coating by adding inorganic fillers, polymers, and specific additives. For example, a high-temperature and wear-resistant ultra-high voltage insulating coating and its preparation method disclosed in patent technical document CN105368309B include, by weight, 35-50 parts of silicone resin, 0.1-0.8 parts of coupling agent, 3-6 parts of titanium dioxide, 7-10 parts of quartz sand, 1-5 parts of natural camphor, 18-23 parts of nano inorganic fillers, 40-55 parts of solvents, 0.3-0.7 parts of curing agent, 1-3 parts of leveling agent, 2-4 parts of anti-settling agent, 0.2-2 parts of dispersant, 0.1-0.5 parts of preservative, and 0.2-0.5 parts of defoaming agent. However, the organic silicone resin-based high temperature resistant insulating coatings prepared by these prior art solutions have relatively high curing temperatures during use, and relatively poor water resistance and adhesion.
[0004] Therefore, according to the above-mentioned related technologies, it is urgent to develop a high temperature resistant insulating coating and a preparation method thereof. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a high temperature resistant insulating coating and a preparation method thereof, so as to solve the problem that the curing temperature of the silicone resin high temperature resistant insulating coating in the prior art is relatively high and the water resistance is relatively poor when used.
[0006] Based on the above purpose, the present invention provides a high temperature resistant insulating coating and a preparation method thereof.
[0007] A high temperature resistant insulating coating comprises the following raw materials in parts by weight:
[0008] Composite liquid 90-95 parts, dispersant 0.7-1.0 parts, leveling agent 0.15-0.3 parts, anti-settling agent 0.4-0.7 parts, defoamer 0.02-0.05 parts, curing agent 12-15 parts;
[0009] The composite liquid is prepared from an organic silicon composite liquid, an acrylic acid composite liquid, a solvent and a filler;
[0010] The organic silicon composite liquid is prepared from octamethylcyclotetrasiloxane, tetraethyl orthosilicate, a silane coupling agent and a block emulsifier;
[0011] The acrylic acid combination liquid is prepared from a block emulsifier, insulating particles, butyl acrylate and methacrylic acid amide;
[0012] The insulating particles are vermiculite particles activated with hydrochloric acid and having a particle size between 2 and 2.5 μm;
[0013] The filler is obtained by mixing aluminum oxide, silicon nitride, mica and zirconium oxide in a mass ratio of 7-10:3-5:7-10:4-6, all of which have a particle size of 30-35 nm.
[0014] Preferably, the preparation method of the block emulsifier is as follows:
[0015] Step A1: After mixing water, tert-butyl mercaptan and sodium hydroxide, acetone is added, the mixture is stirred evenly, carbon disulfide and 2-bromopropionic acid are added in an ice bath, and then the mixture is stirred at room temperature for 22-25 hours, and concentrated hydrochloric acid is added dropwise in an ice bath. After drying the product, the product is recrystallized three times with n-hexane for purification, and dried again to obtain material A;
[0016] Step A2: Add material A and acrylic acid to 1,4-dioxane, stir evenly, then add azobisisobutyronitrile and methyl methacrylate, react at 75-80° C. for 3-4.5 hours, and dry to obtain a block emulsifier.
[0017] Preferably, the mass ratio of water, tert-butyl mercaptan, sodium hydroxide, acetone, carbon disulfide, 2-bromopropionic acid and concentrated hydrochloric acid in step A1 is 90-95: 35-36.5: 27-30: 17-20: 34.2-34.5: 62.7-63: 60-63; the mass ratio of 1,4-dioxane, material A, acrylic acid, azobisisobutyronitrile and methyl methacrylate in step A2 is 45-48: 0.5-0.53: 4.0-4.3: 1.3-1.5: 1.0-1.3.
[0018] Preferably, the solvent is any one of xylene, butanol and hexamethyldisiloxane.
[0019] Preferably, the preparation method of the organosilicon combination liquid is as follows:
[0020] Under a nitrogen atmosphere, water, dodecylbenzenesulfonic acid and block emulsifier are stirred evenly, and after heating to 85-87°C, a mixed solution of octamethylcyclotetrasiloxane, tetraethyl orthosilicate and silane coupling agent is added, and the mixture is reacted for 8.5-10 hours, and then the pH is adjusted to 7-8 to obtain an organosilicon combination liquid.
[0021] Preferably, the mass ratio of the water, dodecylbenzenesulfonic acid, block emulsifier, octamethylcyclotetrasiloxane, tetraethyl orthosilicate and silane coupling agent is 90-95:1.2-1.5:0.7-1:8.2-8.5:0.7-1.0:1.2-1.5.
[0022] Preferably, the preparation method of the acrylic acid composition liquid is as follows:
[0023] Under a nitrogen atmosphere, the block emulsifier, sodium bicarbonate, insulating particles, water, butyl acrylate and methacrylic acid amide were mixed evenly, and the temperature was raised to 85-86.5°C, and then ammonium persulfate was added. The reaction was continued for 4.2-4.5 hours, and the pH was adjusted to 8-9 to obtain an acrylic acid composite liquid.
[0024] Preferably, the mass ratio of the block emulsifier, sodium bicarbonate, insulating particles, water, butyl acrylate, methacrylic acid amide and ammonium persulfate is 17-20: 0.07-0.10: 2.7-3: 70-73: 9.7-10: 0.17-0.2: 1.7-2.
[0025] A method for preparing a high temperature resistant insulating coating, the method for preparing the high temperature resistant insulating coating is as follows:
[0026] Step S1: mixing the organic silicon composite liquid and the acrylic composite liquid, then adding a solvent and a filler, and stirring evenly to obtain a composite liquid;
[0027] Step S2: adding a dispersant to the composite liquid, heating to 75-80°C and stirring at 300-350r / min for 15-30min, then adding a leveling agent, an anti-settling agent, a defoaming agent and a curing agent in sequence while stirring, stirring for another 15-30min, and then grinding and filtering to obtain a high temperature resistant insulating coating.
[0028] Preferably, in step S1, the mass ratio of the organic silicon composite liquid, the acrylic composite liquid, the solvent and the filler is 15-20:20-30:30-35:20-23.
[0029] Beneficial effects of the present invention:
[0030] The invention provides a high-temperature resistant insulating coating and a preparation method thereof. The invention blends an organic silicon resin with a high curing temperature and severely degraded performance at high temperature with an acrylic acid combination liquid, so that the curing temperature of the prepared coating is greatly reduced while the water resistance and thermal stability of the coating are improved; at the same time, the invention further improves the water resistance, heat resistance and insulation capacity of the coating by modifying micron-level insulating particles and filling with nano-level fillers; in order to prevent the non-uniform distribution of insulating particles and fillers from causing the mechanical properties and corrosion resistance of the coating to degrade, the invention prepares a block emulsifier with a low critical micelle concentration, good emulsification and strong foam stability and adds it thereto, so that the components of the coating are evenly distributed and the agglomeration phenomenon is greatly reduced.
[0031] Therefore, compared with the prior art, the high-temperature resistant insulating coating prepared by the present invention has a lower curing temperature, better water resistance, and has a wider application prospect. DETAILED DESCRIPTION
[0032] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0033] Embodiment 1: A high temperature resistant insulating coating and a preparation method thereof, comprising the following steps:
[0034] S1: 90g of water, 35g of tert-butyl mercaptan and 27g of sodium hydroxide were mixed, and then 17g of acetone was added. After stirring, 34.2g of carbon disulfide and 62.7g of 2-bromopropionic acid were added in an ice bath, and then stirred at room temperature for 22h, and then 60g of concentrated hydrochloric acid was added dropwise in an ice bath. After drying, the product was recrystallized three times with n-hexane for purification, and dried again to obtain material A;
[0035] S2: Add 0.5 g of material A and acrylic acid to 45 g of 1,4-dioxane, stir evenly, then add 1.3 g of azobisisobutyronitrile and 1.0 g of methyl methacrylate, react at 75 ° C for 3 h, and dry to obtain a block emulsifier;
[0036] S3: Under a nitrogen atmosphere, 90 g of water, 1.2 g of dodecylbenzene sulfonic acid and 0.7 g of a block emulsifier were stirred evenly, and a mixture of 8.2 g of octamethylcyclotetrasiloxane, 0.7 g of ethyl orthosilicate and 1.2 g of a silane coupling agent was added after heating to 85° C., and the mixture was reacted for 8.5 h, and the pH was adjusted to 7 to obtain an organosilicon composite liquid;
[0037] S4: Under a nitrogen atmosphere, 17 g of block emulsifier, 0.07 g of sodium bicarbonate, 2.7 g of insulating particles, 70 g of water, 9.7 g of butyl acrylate and 0.17 g of methacrylic acid amide were mixed evenly, and 1.7 g of ammonium persulfate was added after heating to 85° C., and the reaction was continued for 4.2 h, and the pH was adjusted to 8 to obtain an acrylic acid composite liquid;
[0038] S5: 15 g of the silicone composite liquid and 20 g of the acrylic composite liquid are mixed, and then 30 g of the solvent and 20 g of the filler are added, and stirred to obtain a composite liquid;
[0039] S6: Add 0.7g of dispersant to 85g of the composite liquid, heat to 75°C and stir at 300r / min for 15min, then add 0.15g of leveling agent, 0.4g of anti-settling agent, 0.02g of defoaming agent and 12g of curing agent in sequence while stirring, stir for another 15min, and then grind and filter to obtain a high temperature resistant insulating coating.
[0040] Embodiment 2: A high temperature resistant insulating coating and a preparation method thereof, comprising the following steps:
[0041] S1: 92g of water, 35.5g of tert-butyl mercaptan and 28g of sodium hydroxide were mixed, and then 18g of acetone was added. After stirring, 34.3g of carbon disulfide and 62.8g of 2-bromopropionic acid were added in an ice bath, and then stirred at room temperature for 23h, and then 61g of concentrated hydrochloric acid was added dropwise in an ice bath. After drying, the product was recrystallized three times with n-hexane for purification, and dried again to obtain material A;
[0042] S2: Add 0.51 g of material A and acrylic acid to 46 g of 1,4-dioxane, stir evenly, then add 1.4 g of azobisisobutyronitrile and 1.1 g of methyl methacrylate, react at 77° C. for 3.5 h, and dry to obtain a block emulsifier;
[0043] S3: Under a nitrogen atmosphere, 92 g of water, 1.3 g of dodecylbenzene sulfonic acid and 0.8 g of a block emulsifier were stirred evenly, and a mixture of 8.3 g of octamethylcyclotetrasiloxane, 0.8 g of ethyl orthosilicate and 1.3 g of a silane coupling agent was added after heating to 86° C., and the mixture was reacted for 9 h, and the pH was adjusted to 7 to obtain an organosilicon composite liquid;
[0044] S4: Under a nitrogen atmosphere, 18 g of a block emulsifier, 0.08 g of sodium bicarbonate, 2.8 g of insulating particles, 71 g of water, 9.8 g of butyl acrylate and 0.18 g of methacrylic acid amide were mixed evenly, and after heating to 85.5° C., 1.8 g of ammonium persulfate was added, and the reaction was continued for 4.3 h, and the pH was adjusted to 8 to obtain an acrylic acid composite liquid;
[0045] S5: 17 g of the silicone composite liquid and 24 g of the acrylic composite liquid were mixed, and then 32 g of the solvent and 21 g of the filler were added, and stirred to obtain a composite liquid;
[0046] S6: Add 0.8g of dispersant to 87g of the composite liquid, heat to 77°C and stir at 320r / min for 20min, then add 0.2g of leveling agent, 0.5g of anti-settling agent, 0.03g of defoaming agent and 13g of curing agent in sequence while stirring, stir for another 20min, and then grind and filter to obtain a high temperature resistant insulating coating.
[0047] Embodiment 3: A high temperature resistant insulating coating and a preparation method thereof, comprising the following steps:
[0048] S1: 94g of water, 36g of tert-butyl mercaptan and 29g of sodium hydroxide were mixed, and then 19g of acetone was added. After stirring, 34.4g of carbon disulfide and 62.9g of 2-bromopropionic acid were added in an ice bath, and then stirred at room temperature for 24h, and then 62g of concentrated hydrochloric acid was added dropwise in an ice bath. After drying, the product was recrystallized three times with n-hexane for purification, and dried again to obtain material A;
[0049] S2: Add 0.52 g of material A and acrylic acid to 47 g of 1,4-dioxane, stir evenly, then add 1.4 g of azobisisobutyronitrile and 1.2 g of methyl methacrylate, react at 79° C. for 4 h, and dry to obtain a block emulsifier;
[0050] S3: Under a nitrogen atmosphere, 94 g of water, 1.4 g of dodecylbenzene sulfonic acid and 0.9 g of a block emulsifier were stirred evenly, and a mixture of 8.4 g of octamethylcyclotetrasiloxane, 0.9 g of ethyl orthosilicate and 1.4 g of a silane coupling agent was added after heating to 86° C., and the mixture was reacted for 9.5 h, and the pH was adjusted to 8 to obtain an organosilicon composite liquid;
[0051] S4: Under a nitrogen atmosphere, 19 g of a block emulsifier, 0.09 g of sodium bicarbonate, 2.9 g of insulating particles, 72 g of water, 9.9 g of butyl acrylate and 0.19 g of methacrylic acid amide were mixed evenly, and after heating to 86° C., 1.9 g of ammonium persulfate was added, and the reaction was continued for 4.4 h, and the pH was adjusted to 9 to obtain an acrylic acid composite liquid;
[0052] S5: 19 g of the silicone composite liquid and 28 g of the acrylic composite liquid were mixed, and then 34 g of the solvent and 22 g of the filler were added, and stirred to obtain a composite liquid;
[0053] S6: Add 0.9g of dispersant to 89g of the composite liquid, heat to 79°C and stir at 340r / min for 25min, then add 0.25g of leveling agent, 0.6g of anti-settling agent, 0.04g of defoaming agent and 14g of curing agent in sequence while stirring, stir for another 25min, and then grind and filter to obtain a high temperature resistant insulating coating.
[0054] Embodiment 4: A high temperature resistant insulating coating and a preparation method thereof, comprising the following steps:
[0055] S1: 95g of water, 36.5g of tert-butyl mercaptan and 30g of sodium hydroxide were mixed, and then 20g of acetone was added. After stirring, 34.5g of carbon disulfide and 63g of 2-bromopropionic acid were added in an ice bath, and then stirred at room temperature for 25h, and then 63g of concentrated hydrochloric acid was added dropwise in an ice bath. After drying, the product was recrystallized three times with n-hexane for purification, and dried again to obtain material A;
[0056] S2: Add 0.53 g of material A and acrylic acid to 48 g of 1,4-dioxane, stir evenly, then add 1.5 g of azobisisobutyronitrile and 1.3 g of methyl methacrylate, react at 80° C. for 4.5 h, and dry to obtain a block emulsifier;
[0057] S3: Under a nitrogen atmosphere, 95 g of water, 1.5 g of dodecylbenzene sulfonic acid and 1.0 g of a block emulsifier were stirred evenly, and a mixture of 8.5 g of octamethylcyclotetrasiloxane, 1.0 g of ethyl orthosilicate and 1.5 g of a silane coupling agent was added after heating to 87° C., and the mixture was reacted for 10 h, and the pH was adjusted to 8 to obtain an organosilicon composite liquid;
[0058] S4: Under a nitrogen atmosphere, 20 g of block emulsifier, 0.10 g of sodium bicarbonate, 3 g of insulating particles, 73 g of water, 10 g of butyl acrylate and 0.2 g of methacrylic acid amide were mixed evenly, and 2 g of ammonium persulfate was added after heating to 86.5° C., and the reaction was continued for 4.5 h, and the pH was adjusted to 9 to obtain an acrylic acid composite liquid;
[0059] S5: 20 g of the silicone composite liquid and 30 g of the acrylic composite liquid are mixed, and then 35 g of the solvent and 23 g of the filler are added, and stirred to obtain a composite liquid;
[0060] S6: Add 1.0g of dispersant to 90g of the composite liquid, heat to 80℃ and stir at 350r / min for 30min, then add 0.3g of leveling agent, 0.7g of anti-settling agent, 0.05g of defoaming agent and 15g of curing agent in sequence while stirring, stir for another 30min, and then grind and filter to obtain a high temperature resistant insulating coating.
[0061] Comparative Example 1:
[0062] Compared with Example 1, this comparative example does not add insulating particles during the preparation of the acrylic acid composition liquid, and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a high-temperature resistant insulating coating is obtained.
[0063] Comparative Example 2:
[0064] Compared with Example 1, this comparative example only replaces the "block emulsifier" with "any one of the anionic emulsifier and the non-ionic emulsifier or their combination", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a high temperature resistant insulating coating is obtained.
[0065] Comparative Example 3:
[0066] Compared with Example 1, this comparative example only replaces the "organic silicone combination liquid and acrylic combination liquid" in the composite liquid preparation process with "organic silicone resin modified with insulating particles", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a high temperature resistant insulating coating is obtained.
[0067] Comparative Example 4:
[0068] Compared with Example 1, this comparative example only replaces the "organic silicone combination liquid and acrylic combination liquid" in the composite liquid preparation process with "acrylic resin modified with insulating particles", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a high temperature resistant insulating coating is obtained.
[0069] Comparative Example 5:
[0070] Compared with Example 1, this comparative example only replaces the "organic silicone combination liquid and acrylic combination liquid" in the composite liquid preparation process with "organic silicone resin", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a high temperature resistant insulating coating is obtained.
[0071] Comparative Example 6:
[0072] Compared with Example 1, this comparative example only replaces the "organic silicone combination liquid and acrylic combination liquid" in the composite liquid preparation process with "acrylic resin", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a high temperature resistant insulating coating is obtained.
[0073] Comparative Example 7:
[0074] Compared with Example 1, this comparative example does not add filler during the preparation of the composite liquid, and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a high-temperature resistant insulating coating is obtained.
[0075] Performance Test:
[0076] Take 11 groups of steel plates with a size of 120mm×50mm, remove the rust on the surface with 1200 mesh sandpaper, then use anhydrous ethanol to ultrasonically clean the steel plates, and blow dry them with a hair dryer for use; place the treated steel plates on the test bench, and use a wire rod coater with a specification of 100μm (Oshiji Precision Tools Co., Ltd.) to apply the high-temperature resistant insulating coatings prepared in Examples 1-4 and Comparative Examples 1-7 on each group of steel plates, respectively, with a wet film thickness of 100μm; after coating, place the sample flat on the test bench, dry it at 45°C for 10h, and obtain a coating sample, and perform performance tests on the prepared coating sample:
[0077] Adhesion test:
[0078] Referring to the test standard of GB / T9286-2021 "Paint and Varnish - Scratching Test", place the high temperature resistant insulating coating sample on a flat and hard operating table, and use a hundred-grid blade to evenly scratch in two directions perpendicular to each other. During this period, pay attention to even force and smooth scratching without shaking, and the scratching should penetrate the coating and touch the metal plate. After scratching, use a soft brush to gently wipe along the diagonal direction of the grid, and then stick the special 3M tape on the entire grid formed by the scratching. Press hard with your fingers to ensure that the tape is in good contact with the coating. When tearing off the tape, the tape should be at a 60° angle to the coating and tear off smoothly and quickly within 1s. The coating adhesion level is evaluated by observing the size of the tearing area, which is divided into 0-5 levels. The adhesion is strongest at level 0 and the worst at level 5. According to this test standard, the adhesion (level) test is carried out on the samples prepared with high temperature resistant insulating coatings prepared in Example 1-Example 4 and Comparative Example 1-Comparative Example 7;
[0079] Contact angle test:
[0080] Referring to the test standard GB / T30693-2014 "Measurement of the contact angle of plastic film with water", a water contact angle tester (OCA-25) was used to test the high temperature resistant insulating coating sample to be tested. The high temperature resistant insulating coating sample was placed on the platform of the contact angle tester, and the contact angle between the sample surface and distilled water was measured. The result was read after the sample was in contact with the liquid to be tested for 30 seconds. Five different positions on the surface of the sample were taken, and the average value was taken as the contact angle (°) of the sample prepared with the high temperature resistant insulating coating prepared by Example 1-Example 4 and Comparative Example 1-Comparative Example 7;
[0081] Impact resistance test:
[0082] Referring to the test standard of GB / T20624.2-2006 "Paints and varnishes - Rapid impact (impact resistance) test, Part 2: Drop hammer test (small area punch)", a paint film impact tester with a weight of 1 kg (TCJ-Ⅱ, Shanghai Leao Testing Instrument Co., Ltd.) was used to test the impact resistance (kg·m) of the samples prepared by the high temperature resistant insulating coatings prepared in Examples 1 to 4 and Comparative Examples 1 to 7;
[0083] Heat resistance test:
[0084] Referring to the test standard of GB / T1735-2009 "Paints and varnishes - Determination of heat resistance", the samples prepared with the high temperature resistant insulating coatings prepared in Examples 1 to 4 and Comparative Examples 1 to 7 were subjected to high temperature treatment for 24 hours at 1000°C using an electric constant temperature blast drying oven (DHG-9140A, Shanghai Qixin Scientific Instrument Co., Ltd.), and then cooled to 25-30°C. Referring to the test standard of GB / T20624.2-2006 "Paints and varnishes - Rapid impact (impact resistance) test, Part II: Drop hammer test (small area punch)", a heat resistance (kg·m) test was performed using a paint film impactor tester with a weight of 1 kg (TCJ-Ⅱ, Shanghai Leao Testing Instrument Co., Ltd.);
[0085] Corrosion resistance test:
[0086] Referring to the test standard of GB / T10125-2021 "Artificial Atmosphere Corrosion Test-Salt Spray Test", the high temperature resistant insulating coating sample was edge-sealed with epoxy putty, and then placed in a salt spray test box (JAY-1127, Zhuhai Jiayi Testing Equipment Co., Ltd.), at 35 ° C, pH = 6.5-7.2, 5% sodium chloride solution was used for 24h salt spray and 24h drying cycle test, and sampling was observed every 48h, and the test time for the appearance of red rust on each sample was recorded. When the last sample appeared red rust, the neutral salt spray test was terminated; according to this test standard, the samples prepared with the high temperature resistant insulating coating prepared in Example 1-Example 4 and Comparative Example 1-Comparative Example 7 were tested for corrosion resistance (h);
[0087] Stickiness test:
[0088] According to the test standard of GB / T1981.2-2009 "Electrical Insulation Paint, Part 2: Test Method", a piece of filter paper made of bleached cotton with a thickness of 200μm and a nominal density of 0.45g / cm2 is placed on the sample, a soft rubber sheet with a thickness of 5mm and a diameter of 20mm is used as an isolation layer, and a cylindrical weight with a bottom contact surface diameter of 20mm and a mass of 500g is applied to the filter paper for 1min. After removing the weight, the following conditions should be checked and judged: due to gravity or slight vibration, the filter paper is separated from the sample, and such a sample surface is called non-sticky; the filter paper is not separated from the sample due to gravity and slight vibration, but is separated by touching it, and the filter paper fibers do not adhere to the sample surface, and such a sample surface is called non-sticky; the filter paper adheres to the sample, and after removing the filter paper, a considerable amount of filter paper fibers remain on the sample, and such a sample surface is called sticky; according to this test standard, the sample prepared with the high temperature resistant insulating coating prepared by Example 1-Example 4 and Comparative Example 1-Comparative Example 7 is tested for viscosity;
[0089] Breakdown voltage test:
[0090] Referring to the test standard of GB / T1981.2-2009 "Electrical Insulation Paint, Part 2: Test Method", the breakdown voltage (kV) of the high temperature resistant insulating coatings prepared in Examples 1 to 4 and Comparative Examples 1 to 7 was tested at a voltage increase rate of 200 V / s at 25°C using a breakdown voltage tester (HT-5 / 20, Guilin Electrical Science Research Institute). Each sample was tested 5 times, and the average value U was taken as the breakdown voltage (kV). The calculation table formula of the corresponding electrical strength is as follows; the test results are shown in Table 1;
[0091] The electrical strength calculation formula is:
[0092] Where, d is the coating thickness (mm);
[0093] Table 1
[0094]
[0095] Data Analysis:
[0096] As can be seen from Table 1, the high temperature resistant insulating coating prepared by the present invention has higher adhesion, water contact angle, impact resistance, heat resistance, corrosion resistance and electrical strength, as well as lower curing temperature;
[0097] This may be because the present invention blends the silicone resin with acrylic composite liquid, which has a high curing temperature and decomposes into a brittle and loose inorganic -Si-O-Si-O-structure at high temperature, shrinks in volume, causes holes in the coating, and leads to a serious decline in performance, so that the curing temperature of the prepared coating is greatly reduced while improving the mechanical properties, water resistance, insulation capacity and thermal stability of the coating. The present invention further improves the water resistance, impact resistance, heat resistance, corrosion resistance and insulation capacity of the coating by modifying micron-level insulating particles and filling with nano-level fillers; in order to prevent the uneven distribution of insulating particles and fillers from causing a decline in the mechanical properties and corrosion resistance of the coating, the present invention prepares a block emulsifier with a low critical micelle concentration, good emulsification and strong foam stability, and adds it thereto, so that the components of the coating are evenly distributed and the agglomeration phenomenon is greatly reduced;
[0098] Comparative Example 1 did not add insulating particles during the preparation of the acrylic acid composition liquid. It can be seen from Table 1 that its impact resistance, heat resistance, corrosion resistance and electrical strength are relatively poor compared with Example 1. This may be because the addition of vermiculite particles with a particle size between 2-2.5 μm activated by hydrochloric acid can make the coating texture more compact, and it will expand in a high temperature environment to fill the pores in the coating, absorb the moisture decomposed by acrylic acid at high temperature, and enhance the combination between the skeleton and the nano-scale filler. The expanded network structure can also hinder the inward migration of oxygen molecules and water molecules of the corrosive medium;
[0099] In Comparative Example 2, "block emulsifier" is replaced by "any one of anionic emulsifier and nonionic emulsifier or a combination thereof". It can be seen from Table 1 that its water resistance, impact resistance, heat resistance, corrosion resistance and electrical strength are relatively poor compared with those of Example 1. This may be because the block emulsifier prepared by the present invention has a smaller critical micelle concentration, better emulsification and foam stability, and can make the components such as insulating particles and fillers more evenly distributed;
[0100] In Comparative Example 3, the "organic silicon combination liquid and acrylic acid combination liquid" in the preparation process of the composite liquid are replaced by "organic silicon resin modified with insulating particles"; in Comparative Example 4, the "organic silicon combination liquid and acrylic acid combination liquid" in the preparation process of the composite liquid are replaced by "acrylic resin modified with insulating particles"; in Comparative Example 5, the "organic silicon combination liquid and acrylic acid combination liquid" in the preparation process of the composite liquid are replaced by "organic silicon resin"; in Comparative Example 6, the "organic silicon combination liquid and acrylic acid combination liquid" in the preparation process of the composite liquid are replaced by "acrylic resin"; As can be seen from Table 1, compared with Example 1 Compared with Comparative Examples 3 to 6, the adhesion, water resistance, impact resistance, heat resistance, corrosion resistance and electrical strength are relatively poor, and the curing temperature is also relatively high. This may be due to the blending of the silicone resin with a high curing temperature and a greatly reduced performance at high temperature with the acrylic acid combination liquid, which greatly reduces the curing temperature of the prepared coating, and improves the mechanical properties, water resistance, insulation ability and thermal stability of the coating. At the same time, the coating is modified with micron-sized insulating particles to further improve the water resistance, impact resistance, heat resistance, corrosion resistance and insulation ability of the coating;
[0101] In Comparative Example 7, no filler was added during the preparation of the composite liquid. It can be seen from Table 1 that its water resistance, impact resistance, heat resistance, corrosion resistance and insulation capacity are relatively poor compared with Example 1. This may be because the coating prepared after filling with nano-scale fillers is more compact, and these fillers are all high-temperature resistant insulating particles. Therefore, the addition of fillers can improve the water resistance, impact resistance, heat resistance, corrosion resistance and insulation capacity of the coating.
[0102] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
[0103] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high temperature resistant insulating coating, characterized in that: The invention comprises the following raw materials in parts by weight: Composite liquid 85-90 parts, dispersant 0.7-1.0 parts, leveling agent 0.15-0.3 parts, anti-settling agent 0.4-0.7 parts, defoamer 0.02-0.05 parts, curing agent 12-15 parts; The composite liquid is prepared from an organic silicon composite liquid, an acrylic acid composite liquid, a solvent and a filler; The organic silicon composite liquid is prepared from octamethylcyclotetrasiloxane, tetraethyl orthosilicate, a silane coupling agent and a block emulsifier; The acrylic acid composition liquid is prepared from a block emulsifier, insulating particles, butyl acrylate and methacrylic acid amide; The insulating particles are vermiculite particles activated with hydrochloric acid and having a particle size between 2 and 2.5 μm; The filler is obtained by mixing aluminum oxide, silicon nitride, mica and zirconium oxide in a mass ratio of 7-10:3-5:7-10:4-6, all of which have a particle size of 30-35 nm.
2. The high temperature resistant insulating coating according to claim 1, characterized in that: The preparation method of the block emulsifier is as follows: Step A1: After mixing water, tert-butyl mercaptan and sodium hydroxide, acetone is added, the mixture is stirred evenly, carbon disulfide and 2-bromopropionic acid are added in an ice bath, and then the mixture is stirred at room temperature for 22-25 hours, and concentrated hydrochloric acid is added dropwise in an ice bath. After drying the product, the product is recrystallized three times with n-hexane for purification, and dried again to obtain material A; Step A2: Add material A and acrylic acid to 1,4-dioxane, stir evenly, then add azobisisobutyronitrile and methyl methacrylate, react at 75-80° C. for 3-4.5 hours, and dry to obtain a block emulsifier.
3. The high temperature resistant insulating coating according to claim 2, characterized in that: The mass ratio of water, tert-butyl mercaptan, sodium hydroxide, acetone, carbon disulfide, 2-bromopropionic acid and concentrated hydrochloric acid in step A1 is 90-95: 35-36.5: 27-30: 17-20: 34.2-34.5: 62.7-63: 60-63; the mass ratio of 1,4-dioxane, material A, acrylic acid, azobisisobutyronitrile and methyl methacrylate in step A2 is 45-48: 0.5-0.53: 4.0-4.3: 1.3-1.5: 1.0-1.
3.
4. The high temperature resistant insulating coating according to claim 1, characterized in that: The solvent is any one of xylene, butanol and hexamethyldisiloxane.
5. The high temperature resistant insulating coating according to claim 1, characterized in that: The preparation method of the organosilicon combination liquid is as follows: Under a nitrogen atmosphere, water, dodecylbenzenesulfonic acid and block emulsifier are stirred evenly, and after heating to 85-87°C, a mixed solution of octamethylcyclotetrasiloxane, tetraethyl orthosilicate and silane coupling agent is added, and the mixture is reacted for 8.5-10 hours, and then the pH is adjusted to 7-8 to obtain an organosilicon combination liquid.
6. The high temperature resistant insulating coating according to claim 5, characterized in that: The mass ratio of the water, dodecylbenzenesulfonic acid, block emulsifier, octamethylcyclotetrasiloxane, tetraethyl orthosilicate and silane coupling agent is 90-95: 1.2-1.5: 0.7-1: 8.2-8.5: 0.7-1.0: 1.2-1.
5.
7. The high temperature resistant insulating coating according to claim 1, characterized in that: The preparation method of the acrylic acid composition liquid is as follows: Under a nitrogen atmosphere, the block emulsifier, sodium bicarbonate, insulating particles, water, butyl acrylate and methacrylic acid amide were mixed evenly, and the temperature was raised to 85-86.5°C, and then ammonium persulfate was added. The reaction was continued for 4.2-4.5 hours, and the pH was adjusted to 8-9 to obtain an acrylic acid composite liquid.
8. The high temperature resistant insulating coating according to claim 7, characterized in that: The mass ratio of the block emulsifier, sodium bicarbonate, insulating particles, water, butyl acrylate, methacrylic acid amide and ammonium persulfate is 17-20: 0.07-0.10: 2.7-3: 70-73: 9.7-10: 0.17-0.2: 1.7-2.
9. A method for preparing a high temperature resistant insulating coating according to any one of claims 1 to 8, characterized in that: The preparation method of the high temperature resistant insulating coating is as follows: Step S1: mixing the organic silicon composite liquid and the acrylic composite liquid, then adding a solvent and a filler, and stirring evenly to obtain a composite liquid; Step S2: adding a dispersant to the composite liquid, heating to 75-80°C and stirring at 300-350r / min for 15-30min, then adding a leveling agent, an anti-settling agent, a defoaming agent and a curing agent in sequence while stirring, stirring for another 15-30min, and then grinding and filtering to obtain a high temperature resistant insulating coating.
10. The method for preparing the high temperature resistant insulating coating according to claim 9, characterized in that: The mass ratio of the organic silicon composite liquid, the acrylic composite liquid, the solvent and the filler in step S1 is 15-20: 20-30: 30-35: 20-23.
Citation Information
Patent Citations
Nanometer anti-corrosion thermal insulation coating
CN109321058A
Water-based high-temperature-resistant special organosilicon coating and preparation method thereof
CN110885630A
Preparation method of reactive macromolecular emulsifier
CN111217967A
Inorganic filler dispersion liquid, super-hydrophobic insulating wear-resistant coating and preparation method
CN115322612A
High-temperature insulating paint as well as preparation method and application thereof
CN116904112A
